Effect of beinaglutide combined with metformin versus aspart 30 with metformin on metabolic profiles and antidrug antibodies in patients with type 2 diabetes: a randomized clinical trial - Han, Chen-Yu; Lu, Jia-Ping; Ye, Xiao-Mei; Jin, Hai-Ying; Xu, Wei-Wei; Wang, Ping; Zhang, Min (Frontiers in Endocrinology, 2023)
Objective This prospective study aimed to evaluate the effect of beinaglutide combined with metformin versus aspart 30 with metformin on metabolic profiles and antidrug antibodies (ADAs) in patients with type 2 diabetes (T2D). Methods A total of 134 eligible participants were randomly assigned to the test group and the control group. Patients in the test group were treated with beinaglutide and metformin, whereas patients in the control group were randomly treated with aspart 30 and metformin, with a follow-up period of 6 months. The metabolic profiles and ADAs over 6 months were evaluated. Results After 6 months, 101 (75.37%) patients completed the study. Compared with the control group, the beinaglutide group had significant reductions in 2-h postprandial blood glucose (2hBG) and low blood glucose index (LBGI). Glycated hemoglobin (HbA1c) decreased in both groups relative to baseline. In the test group, one had treatment-emergent beinaglutide ADAs. Significant reductions in triglycerides (TG), non-fasting TG, weight, waist circumference (WC), and body mass index (BMI) were observed. The values of insulin sensitivity index (HOMA-IR) were decreased to a statistically higher degree with beinaglutide treatment. Conclusion Beinaglutide reduces metabolic dysfunction, LBGI, and weight in patients of T2D with a low risk of ADAs. Beinaglutide may offer the potential for a disease-modifying intervention in cardiovascular disease (CVD). Clinical trial registration www.chictr.org.cn, identifier ChiCTR2200061003.